Family Climate and Peer Pressure as Predictors of Academic Achievement Motivation of Secondary School Students in Enugu State, Nigeria - Ogo Egbo, Juliet; C. Omeje, Joachim; C. Nwefuru, Bartholomew (International Journal of Psychosocial Rehabilitation, 2024)
This study investigated family climates and peer pressure as correlates of students’ academicachievement motivation in public secondary schools in Agbani Education zone, Enugu State.The study adopted correlational design. The population of the study comprised 8086 studentsin public secondary schools in Agbani Education zone, Enugu State. The sample for the studycomprised 480 students in public secondary schools drawn using multistage samplingtechniques. The instruments used for collecting data for the study were questionnaires viz:Family Climate Questionnaire (FCQ), Peer Pressure Questionnaire (PPQ) and AcademicAchievement Motivation Questionnaire (AAMQ). The instruments were validated by twoexperts in the field of Guidance Counselling and one in Measurement and Evaluation. A trialtest of the instrument was conducted, and the reliability of the instrument was computedusing Cronbach Alpha method. The direct delivery and retrieval method was used inadministering the questionnaire. The research questions and hypotheses were analyzed usingPearson’s product moment correlation coefficient and simple linear regression. The study'sfindings revealed that students were influenced by peer pressure in their academicachievement motivation in Agbani Education Zone in Enugu State. Recommendations weremade, which include that the state government through the state ministry of education, shouldcollaborate with school principals and school guidance counsellors to organize orientationon the influence of peers on academic achievement motivation of students.